2018
DOI: 10.3389/fneur.2017.00693
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Positive and Negative Sleep Variables Differentially Affect Cellular Immune Activity in a Breast Cancer Survivor: A Time-series Analysis Approach

Abstract: This study on a breast cancer survivor suffering from cancer-related fatigue (CaRF) and depression investigated the bidirectional relationship between cellular immune activity and subjective sleep. The 49-year-old patient (breast cancer diagnosis 5 years before the study, currently in remission) collected her full urine output for 28 days in 12-h intervals (8:00 p.m. to 8:00 a.m. and 8:00 a.m. to 8:00 p.m.). These urine samples were used to determine urinary neopterin (cellular immune activation marker) and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…In conclusion, this integrative single-case study on a breast cancer survivor suffering from depression and fatigue showed that positive emotional states such as elevated mood can be both positively and negatively correlated with IL-6 – in both directions of effect, with different temporal delays and intertwined with feedback circuits. Such findings confirm recent data from our working group on the complexity of emotion–immune interplay under conditions of “life as it is lived” ( Schubert et al, 2003 , 2006 , 2012 , 2015 ; Haberkorn et al, 2013 ; Singer et al, 2018 ). The results of this study again raise the possibility that data inconsistency in current PNI research may result from not taking the complex functional aspects of life-science data into account.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In conclusion, this integrative single-case study on a breast cancer survivor suffering from depression and fatigue showed that positive emotional states such as elevated mood can be both positively and negatively correlated with IL-6 – in both directions of effect, with different temporal delays and intertwined with feedback circuits. Such findings confirm recent data from our working group on the complexity of emotion–immune interplay under conditions of “life as it is lived” ( Schubert et al, 2003 , 2006 , 2012 , 2015 ; Haberkorn et al, 2013 ; Singer et al, 2018 ). The results of this study again raise the possibility that data inconsistency in current PNI research may result from not taking the complex functional aspects of life-science data into account.…”
Section: Discussionsupporting
confidence: 90%
“…This study is part of a wider project using the “integrative single case study” design ( Schubert et al, 1999 , 2012 ) to investigate the impact of emotionally meaningful daily incidents on stress system activity in breast cancer survivors suffering from cancer-related fatigue. Results from this study have already been published ( Haberkorn et al, 2013 ; Singer et al, 2018 ).…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…This integrative single-case study is part of a larger project on breast cancer survivors that examines the effects of emotionally meaningful incidents on stress system activity. Various results dealing with this patient have already been published (22,23,35,36).…”
Section: Methodsmentioning
confidence: 94%